A common-to-come Fictionalising the common at the crossover of theatre and history - de la Serna, Andrea (Re-visiones, 2024)
This paper deals with the complicities between history and theatre, starting from the deleuzian concept of people to-come (peuple à venir) and from the images of the Peter Brook’s film Marat/Sade. Both concept and image will contribute to understand the meaning of fictionalizing the common and from which ontological, aesthetic and political proposals we can face the issue. The tension between aesthetics and politics will constantly appear through the text, and it will help us to think about a concept of “common” that does not accommodate neither by a representational thought nor an account of the historic understood as the process of major revolutions. Both proposals will complete each other and will help me to think about the meaning of a common world-to-come.